Assessment As Learning in the Writing Process: Development of Self-Writing Assessment for Guiding Students in Scientific Writing - Rini, Titis Angga; Cahyanto, Bagus; Nuraini, Ni Luh Sakinah (Proceedings Series of Educational Studies, 2024)
Scientific writing is a challenge for students because the writing is bound by various scientific conventions in terms of content and grammar in each part. Following up on this condition, in this study, a self-writing assessment instrument was developed for guidance on writing research papers students. This study uses the ADDIE model with five stages of steps considering the practicality of the steps for developing learning products. During product development, data on content validity, interrater reliability, and user tests were collected for product application. The results were analyzed descriptively, quantitatively, statistically, and qualitatively, describing each product's feasibility qualifications obtained by collecting questionnaires, field notes, and documentation techniques. At the end of the study, it was found that the self-writing assessment instrument was successfully developed and could be used in guiding the writing of research papers, especially in the presentation of content and grammar. Furthermore, self-writing assessment instruments can be applied to maximize the writing process at the post-revising and editing stage.